2011
DOI: 10.1063/1.3625946
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tetragonal distortion on the topological electronic structure of the half-Heusler compound LaPtBi from first principles

Abstract: The electronic structures of tetragonally distorted half-Heuselr compound LaPtBi in the C1 b structure are investigated in the framework of density functional theory using the full potential linearized augmented plane with local spin density approximation method. The calculation results show that both the band structures and the Fermi level can be tuned by using either compressive or tensile in-plane strain. A large bulk band gap of 0.3 eV can be induced through the application of a compressive in-pane strain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…The recent discoveries of giant linear MR in Bi 2 Se 3 1011 and Bi 2 Te 3 1213 topological insulators (TIs) has brought renewed interest to linear MR. Because of their unusual surface states that are naturally zero bandgap with linear dispersion, TIs provide a perfect platform on which to study the origin of linear MR. Because some Heusler compounds have recently been predicted to be TIs141516, it is worth investigating whether large linear MR can also be observed in Heusler alloys. Considerable efforts have been devoted to the study of the electric structures and transport properties of a number of Heusler-based TIs171819202122232425. X-ray photoelectron spectroscopy results have shown that such Heusler-based materials as YPtSb, LaPtBi, LuPtSb and LuPdBi are gapless semiconductors with very high mobility212224 although large linear MR and desired Shubnikov-de Haas (SdH) quantum oscillations have not been observed experimentally in these materials.…”
mentioning
confidence: 99%
“…The recent discoveries of giant linear MR in Bi 2 Se 3 1011 and Bi 2 Te 3 1213 topological insulators (TIs) has brought renewed interest to linear MR. Because of their unusual surface states that are naturally zero bandgap with linear dispersion, TIs provide a perfect platform on which to study the origin of linear MR. Because some Heusler compounds have recently been predicted to be TIs141516, it is worth investigating whether large linear MR can also be observed in Heusler alloys. Considerable efforts have been devoted to the study of the electric structures and transport properties of a number of Heusler-based TIs171819202122232425. X-ray photoelectron spectroscopy results have shown that such Heusler-based materials as YPtSb, LaPtBi, LuPtSb and LuPdBi are gapless semiconductors with very high mobility212224 although large linear MR and desired Shubnikov-de Haas (SdH) quantum oscillations have not been observed experimentally in these materials.…”
mentioning
confidence: 99%
“…Similar to the half-Heusler compounds [18], these quaternary Heusler compounds with topologically insulating property cannot have a non-zero band gap at C point at the Fermi level because of the cubic symmetry. The cubic symmetry protects the degeneration of C 8 states not to be destroyed.…”
Section: Resultsmentioning
confidence: 97%
“…The earlier reports showed that the inverse Heusler structure can be considered as two hybridized interpenetrating zinc-blendes, which are X-X and M-Z [18]. Quaternary Heusler compounds have the chemical formula of XX'MZ, where X, X', and M are different transition metals, and Z is a main group element.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations